PREVALENCE OF GASTROINTESTINAL NEMATODES PARASITES FROM SHEEP AND EVALUATION OF SOME ANTHELMINTHIC RESISTANCE IN ERBIL GOVERNORATE - Khalid Jabar Aziz; Ahmed Ibrahim Ahmed; Sherzad Othman Abdullah (Basrah Journal of Veterinary Research)
Prevalence and anthelmintic resistance status of gastrointestinal nematodes in 430 sheep investigate by faecal examination was conducted in Qushtapa, Khabat, Benslawa, Salahaddin subdistricts in Erbil, from April to July 2012. The mean eggs per gram (EPG) count determined by using modified McMaster technique, showed that (40.46%) of the sheep were infested, the higher infection was 17.2% Nematodirus spp., 13.02% Strongylus spp., 4.18% Marshaligia spp., 2.79% Trichurus spp. and 3.25% with coccidia. Four farms were selected randomly each divided to control and three treatment groups: Levamisol, Albendazole and Ivermectin groups. Anthelmintic efficacy was measured after treatment dates were investigated with faecal egg count reduction test, the FECRT percentage for Levamisol in sheep ranged from 80.3 to 94.7 which show most effective in Khabat with FECRT of 94.7% while with Albendazole ranged from 75.5% to 80.2%, suspected resistant in all group, but the injectable Ivermectin in sheep ranged from 85.2 to 94.8 and show effective in Bnaslawa and Salahaddin with FECR of 94.6% and 94.8% respectively. All the anthelmintic were found to be low effective, but resistance to Albendazole was suspected. Based on the findings, it was concluded that development of anthelmintic resistance could be prevented by avoiding frequent dosing and under dosing, while strategic deworming should be practiced by both animal health workers and animal owners.